2013
DOI: 10.1080/02673843.2013.785437
|View full text |Cite
|
Sign up to set email alerts
|

Academic self-efficacy as a resilience factor among adjudicated girls

Abstract: This study focuses on understanding learning disabilities (LDs) as a non-specific risk factor for delinquency among adolescent at-risk girls and investigates academic, social and emotional self-efficacy of adolescent girls with and without LDs in three educational settings: youth protection authority facilities (YPA), special education (SE) and general education (GE). In addition to self-efficacy variables, the study also gathered emotional-behavioural data. The sample included 46 girls adjudicated in YPA faci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 115 publications
1
15
0
Order By: Relevance
“…This research found that academic self‐efficacy is associated with subsyndromal symptomology as well. The present study also adds to a growing body of evidence that suggests academic self‐efficacy is an achievable resilience factor for secondary students at risk for academic failure and dropout (Amitay & Gumpel, ; Mann, Smith, & Kristjansson, ; Peguero & Shaffer, ). Interestingly, the findings of this study are inconsistent with the overwhelming research suggesting gender differences in internalizing and externalizing problems (Bongers et al., ; Daughters et al., ; Hankin et al., ; Leadbeater et al., ; Rudolph, ; Scaramella et al., ; Telzer & Fuligni, ), as academic self‐efficacy was found to be a stronger predictor of both variables than gender.…”
Section: Discussionmentioning
confidence: 58%
“…This research found that academic self‐efficacy is associated with subsyndromal symptomology as well. The present study also adds to a growing body of evidence that suggests academic self‐efficacy is an achievable resilience factor for secondary students at risk for academic failure and dropout (Amitay & Gumpel, ; Mann, Smith, & Kristjansson, ; Peguero & Shaffer, ). Interestingly, the findings of this study are inconsistent with the overwhelming research suggesting gender differences in internalizing and externalizing problems (Bongers et al., ; Daughters et al., ; Hankin et al., ; Leadbeater et al., ; Rudolph, ; Scaramella et al., ; Telzer & Fuligni, ), as academic self‐efficacy was found to be a stronger predictor of both variables than gender.…”
Section: Discussionmentioning
confidence: 58%
“…In a sample of Chinese youth from post-adjudication facilities in Hong Kong, the LD (specific reading disability, SRD) and ADHD comorbidity subgroup showed impairments in executive functioning (interference control, specifically) and significantly higher delinquency severity compared to either SRD or ADHD groups (Poon & Ho, 2014). Importantly, researchers have demonstrated the connection between the presence of LD and low academic self-efficacy beliefs, which, in turn, lower academic achievement and worsen prospects for educational attainment (Amitay & Gumpel, 2015). In general, as a group, JJ-involved youth are characterized by a host of exogenous problems, such as victimization (Karnik, 2001) and deprived environments (Asscher, Van der Put, & Stams, 2015), and endogenous difficulties, such as aggression and substance abuse (Andreassen, 2015; Heynen, van der Helm, Cima, Stams, & Korebrits, 2017; Sawyer, Borduin, & Dopp, 2015).…”
Section: Academic Difficulties and Ld Among Jj-involved Youthmentioning
confidence: 99%
“…Resilience is based on self-efficacy as it arises out of the belief in one's ability to deal with change, while the abilities of resilient individuals lead to their self-efficacy (Djourova et al , 2020; Lightsey, 2006). Self-efficacy beliefs are a mobilizing mechanism for self-control in life-threatening events (Amitay and Gumpel, 2015) and an important factor in enhancing resilience, as they are constantly changing and triggered immediately by adverse events. High self-efficacy beliefs play an important role in the development and maintenance of resilience (Benight and Cieslak, 2011).…”
Section: Introductionmentioning
confidence: 99%